Analysis of Definite Integral Material Topics for Improve Student Learning Using Apriori Algorithm - N. PRIYA DHARSHINNI (Universitas Medan Area, 2021)
Definite Integral is one of the most important subjects in calculus. The use of integrals that must be studied is calculating the area and drawing curves based on the equation of functions. However, there are still many students have difficult to understand integral material, especially definite integral. Most students have difficult to understand Integral learning because they do not understand the basic and material that needs to be mastered. The purpose of this study is to find a pattern of relationship to the understanding the topic of integral material about calculation and drawing of integral curves using apriori algorithm. Apriori algorithms can be used to determine learning patterns and linkages between definite integral material. Apriori algorithms can be used to determine learning patterns and linkages between definite integral material. The results of this study indicate that understanding of the material is the topic of calculation with 1 functional equation and 2 functional equations, and the depiction of integral curves at X and Y coordinates with a confidence value of 96% and basic integral material such as understanding basic integral techniques, definite integral formulas, calculations and curve depiction on cartesian diagram coordinates X and Y with a confidence value of 76%.